2011
DOI: 10.1007/s10067-011-1899-7
|View full text |Cite
|
Sign up to set email alerts
|

MRI identifies plantar plate pathology in the forefoot of patients with rheumatoid arthritis

Abstract: Previous cadaveric studies have suggested that forefoot deformities at the metatarsophalangeal (MTP) joints in patients with rheumatoid arthritis (RA) might result from the failure of the ligamentous system and displacement of the plantar plates. This study aimed to examine the relationship between plantar plate pathology and the rheumatoid arthritis magnetic resonance imaging score (RAMRIS) of the lesser (second to fifth) MTP joints in patients with RA using high-resolution 3 T magnetic resonance imaging (MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
(18 reference statements)
2
13
1
1
Order By: Relevance
“…A recent MRI study has demonstrated that focal deficiencies attributed to plantar plate pathology of the lesser (second to fifth) MTP joints are common in the forefoot of patients with RA and associated with synovitis, bone edema, and bone erosion 13 .…”
Section: Rheumatologymentioning
confidence: 99%
“…A recent MRI study has demonstrated that focal deficiencies attributed to plantar plate pathology of the lesser (second to fifth) MTP joints are common in the forefoot of patients with RA and associated with synovitis, bone edema, and bone erosion 13 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Regarding construct validity, three studies were deemed to have MRI-data of high quality 16 20 22. Synovitis was associated with plantar plate pathology, which represents a failure of the ligamentous system and displacement of the plantar plates of the forefoot leading to malformation 22. When patients were followed for up to 24 months, MRI-detected synovitis was not associated with radiographic damage 20.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of MRI over radiography, apart from the absence of ionizing radiation, is the superior imaging of the structures in RA, such as synovial tissue, tendons, sheaths, ligaments, bone, and cartilage (Baan et al 2011). A recent MRI study has demonstrated that focal deficiencies attributed to plantar plate pathology of the lesser (second to fifth) MTP joints are common in the forefoot of patients with RA and associated with synovitis, bone oedema, and bone erosion (Siddle et al 2012a). In a more recent study, MRI arthrography demonstrated pathology at 18 of 28 lesser MTP joints (64%) examined in 15 patients with RA (Siddle et al 2012b).…”
Section: Clinical Examinationmentioning
confidence: 97%